2003
DOI: 10.1289/ehp.6039
|View full text |Cite
|
Sign up to set email alerts
|

Nerve cell damage in mammalian brain after exposure to microwaves from GSM mobile phones.

Abstract: The possible risks of radio-frequency electromagnetic fields for the human body is a growing concern for our society. We have previously shown that weak pulsed microwaves give rise to a significant leakage of albumin through the blood-brain barrier. In this study we investigated whether a pathologic leakage across the blood-brain barrier might be combined with damage to the neurons. Three groups each of eight rats were exposed for 2 hr to Global System for Mobile Communications (GSM) mobile phone electromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
245
4
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(266 citation statements)
references
References 17 publications
10
245
4
7
Order By: Relevance
“…Another remarkable observation in our studies is the fact that a significant neuronal damage is seen in rat brains 50 days after a 2 hour exposure to GSM at specific absorption rates of 200 and 20 mW/kg [25]. Also 28 days after 2 hours of real GSM exposure (at power density levels of 2 and 0.2 mW/kg) the same type of neuronal damage is seen (article submitted for publication).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Another remarkable observation in our studies is the fact that a significant neuronal damage is seen in rat brains 50 days after a 2 hour exposure to GSM at specific absorption rates of 200 and 20 mW/kg [25]. Also 28 days after 2 hours of real GSM exposure (at power density levels of 2 and 0.2 mW/kg) the same type of neuronal damage is seen (article submitted for publication).…”
Section: Introductionsupporting
confidence: 71%
“…When 25 microlitres of rat albumin is infused into rat neostriatum, 10 and 30, but not 3 mg/ml albumin causes neuronal cell death and severe axonal damage. It also causes leakage of endogenous albumin in and around the area of neuronal damage In our studies, we have observed albumin leakage out into the brain parenchyma 14 days [7] and 50 days [25] after 2 hours of EMF exposure to a real GSM programmable mobile phone in the 900 MHz band (at specific absorption rates of 200, 20 and 2 mW/kg for the 50 days post-exposure study and the same energy levels plus 0.2 mW/kg for the 14 days post-exposure study).…”
Section: Introductionmentioning
confidence: 49%
“…[15] Most animal studies have reported evidence for neuronal damage in the cortex, hippocampus, basal ganglia, reduced memory functions, increased permeability of the bloodbrain barrier, and signs of neuronal damage in the brains of rats exposed to microwaves from GSM mobile phones. [16][17][18] Whereas, a study by Grafström et al showed no significant alteration in the histopathological parameters, when comparing the GSM-exposed animals to the sham-exposed controls. [19] The International Agency for Research on Cancer which is a part of the World Health Organization has grouped these radiations as Group 2B carcinogens implying that they are possibly carcinogenic.…”
Section: Discussionmentioning
confidence: 92%
“…Latency of Wave I is increased when there is damage to auditory nerve or there is a cochlear pathology. Electromagnetic frequencies of mobile phones cause damage to nerves [20]. Since, auditory nerve is closest to electromagnetic field of mobile phone; it is the most likely nerve to be damaged.…”
Section: Discussionmentioning
confidence: 99%